PENERAPAN MODEL PEMBELAJARAN SQ3R DALAM USAHA MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Agus Rahmat; Jajang Rahmatudin; Rifqi Hidayat (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2019)
This research is motivated by the poor ability of mathematical reasoning and student motivation.The research is Quasi Experimental research. The research design is used NonequivalentControl Group Design. The population is class VIII SMP Islamiyah Weru Cirebon in academicyear 2016/2017. The technique in the research is Sampling Purposive. Sample involves eighthgrade students, the 33 class VIII A as an experimental class and class VIII B of the 36 studentsas the control class. Based on the result of the difference of the average of post-test using the testof Independent-Sample T Test equals Sig. (1-tailed) score 0,000 < 0,05 means Ho rejected, showthe ability of students learning mathematical reasoning using models SQ3R betterthan students whose learning conventionally. Then the difference of the average using ofN-gain using the test of Independent-Sample T Test equals Sig. score (1-tailed) 0,000 < 0,05means Ho rejected, show increasing the mathematical reasoning skills students arelearning to use the model SQ3R better than students whose learning conventionally.Keywords: SQ3R and ability of mathematical reasoning